Pengaruh Penambahan Liquid Suction Heat Exchanger Terhadap Performa Mesin Pendingin Menggunakan R404A - Roswati Nurhasanah; Prayudi Prayudi (Sekolah Tinggi Teknik - PLN, 2016)
One method to improve the performance of vapor compression refrigeration system using subcooling. The liquid line suction heat exchanger (LLHX) sub-cooler is a method to increase the cooling capacity of the evaporator by lowering temperature at the condenser outlet. LLHX always Increased effect of refrigeration, work of compressor and heat rejected in the condenser. The results Showed that LLHX lowering condenser exit temperature and exit temperature compressor increases as a result of superheat. LLHX exit temperature compressor with stable at 28oC compared to 16oC on the operation without LLHX in 60 minutes. The experimental results also showed that the evaporation temperature decreases of 15.2 with the addition LLHX be 17.4oC. and the latter can increase the value of COP of 2.85 until 3.5.